2019
DOI: 10.6026/97320630015824
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification, characterization and phylogenetic analysis of Dicer-like (DCL) gene family in Coffea arabica

Abstract: A fine-tuned RNA interference (RNAi) pathway has been developed by plants to restrain distinct biological processes in various life stages including stress responses, development and maintenance of genome integrity. The Dicer-Like (DCL) proteins starts the RNAi process by producing complementary double-stranded RNAs (dsRNAs) into small RNA duplexes (21-24 nucleotides) trigger the RNAi process. Nevertheless, these members of RNAi pathway have not been deciphered in one of the most economically important plant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
2
2
Order By: Relevance
“…S1); two DCL3 copies were found to be similar in sequence but from different parental subgenomes; and finally, only one CaDCL4 copy was found, from the C. eugenioides' subgenome (Table S1). Compared to other works, here we found five more DCLs than previously described by Mosharaf et al (2019) and eight more than those published by Noronha Fernandes-Brum et al (2017). Details of all the sequences are available in Table S1.…”
Section: Characterization Of DCL and Ago Proteins In The Coffea Arabi...contrasting
confidence: 59%
“…S1); two DCL3 copies were found to be similar in sequence but from different parental subgenomes; and finally, only one CaDCL4 copy was found, from the C. eugenioides' subgenome (Table S1). Compared to other works, here we found five more DCLs than previously described by Mosharaf et al (2019) and eight more than those published by Noronha Fernandes-Brum et al (2017). Details of all the sequences are available in Table S1.…”
Section: Characterization Of DCL and Ago Proteins In The Coffea Arabi...contrasting
confidence: 59%
“…The DCL2 clade was the group with the highest number of CaDCLs homologs, eight, but only CaDCL2.1 presented the complete main domains (Table S1 and Figure S1); two DCL3 copies were found to be similar in sequence but from different parental subgenomes; and finally, only one CaDCL4 copy was found, from the C. eugenioides ' subgenome (Table S1). Compared to other works, here we found five more DCLs than previously described by Mosharaf et al (2019) and eight more than those published by Noronha Fernandes‐Brum et al (2017). Details of all the sequences are available in Table S1.…”
Section: Resultscontrasting
confidence: 57%
“…The analysis also suggested a significant difference in the enrichment of cis-regulatory elements in MBF1c genes including TGA-element, AT-rich sequence, wun-motif, AuxRR-core and telo-motif respectively. Studies suggested that the identified cis-regulatory elements play important role in cotton fiber development, transcriptional activity of genes as well as in response to drought stress (Huang et al 2020;Li et al 2006;Mosharaf et al 2019;Tjaden and Coruzzi 1994). These results evidenced the MBF1 family genes are highly conserved with important cis-regulatory elements.…”
Section: Potential Biological Role Of Mbf1 Genesmentioning
confidence: 75%